Moving to microservices : using domain-driven design to break down the monolith : LiveLessons - Gomez, Maria; Safari eBooks ([Place of publication not identified] : Addison-Wesley, 2017)
"Agile practices and techniques, such as continuous delivery, are about being able to react to changes rapidly. However, putting them into practice when you have a big monolith application can be difficult. A microservice architecture offers one solution. Breaking the monolith and moving toward a microservice architecture can offer significant advantages to organizations, in terms of improving team autonomy and increasing frequency of change. These benefits, however, come at a cost. Teams are not always aware of the additional complexity associated with distributed systems and the level of maturity and investment that organizations require to succeed with them. In 'Moving to Microservices LiveLessons', Maria Gomez, a lead consultant at Thoughtworks, introduces considerations and best practices for moving to microservices. Gomez first defines the prerequisites for moving into a microservice architecture. She helps you understand the relative cost of the changes involved so that you can decide whether they are worth it for your organization. With step-by-step examples using domain-driven design (DDD) and other extreme programming (XP) techniques, she then demonstrates how to break down your existing monolith into independent, cooperating entities."--Resource description page.
Presenter, Maria Gomez.
Title from title screen (viewed May 8, 2017).
Keywords: Application software -- Development; Java (Computer program language); Distributed operating systems (Computers); Computer architecture; Electronic books